Analysis of Small Business Performance in Terms of Islamic Financial Literacy and Inclusion - Antin Rakhmawati; Muhammad Nizar (MALIA: Jurnal Ekonomi Islam, 2023)
The main objective of this research is to investigate the level of knowledge of Islamic finance among small businesses and its impact on Islamic financial inclusion. The study adopts an explanatory research design and employs a quantitative approach. A total of 193 small business owners in Malang City, UK, participated as respondents in the study. The sampling technique used was side proportional random sampling with a 95% confidence level. The collected data were analyzed using linear regression analysis.The findings of the study reveal that there is a significant positive relationship between Islamic financial literacy and Islamic financial inclusion. Moreover, the study also highlights the significant influence of Islamic financial inclusion on the performance of small businesses in Malang City. These results align with previous research and provide valuable implications and directions for future studies in this field.